Expression and molecular analysis of DsRed and gfp fluorescent genes in tobacco (Nicotiana tabacum L.) - Kati OVEN; Zlata LUTHAR (Acta Agriculturae Slovenica)
Agrobacterium-mediated transformation of tobacco leaf disks with Agrobacterium tumefaciens (A. t.) strain LBA4404 and two plasmids (pCAMBIA1390-DsRed and pART27 2mgfp5-ER) was used for introducing red fluorescent gene (DsRed), green fluorescent gene (gfp) and corresponding selection genes (hptII for resistance to antibiotic hygromycin and nptII for resistance to kanamycin) into leaf discs of tobacco (Nicotiana tabacum L.). Epifluorescent microscopy with the appropriate set of filters did not reveal phenotypic expression of the DsRed gene in 6.9 % of regenerants and the gfp gene in 1.3 % of regenerants that were successfully grown on selective medium. The duplex PCR method also did not confirm the presence of fragments specific to DsRed or gfp genes in these regenerants, while the presence of fragments characteristic of selection genes hptII and nptII was confirmed. A built-in nptII gene mutation, a deletion, was detected in one regenerant. Out of the 139 regenerants generated after the transformation of A. t.-pCAMBIA1390-DsRed, 38 or 25.5 % successfully grew only on non-selective medium; after transformation with A. t.-pART27 2mgfp5-ER 9 or 5.4 % of the 161 generants grew successfully. PCR analysis confirmed in all regenerants the presence of fragments characteristic of both transgenes, which were not expressed or were silenced. The effectiveness of transformation after infection with A. t.-pCAMBIA1390-DsRed was 93.1 %, and 98.7 % after infection with A. t.-pART27 2mgfp5-ER. We established that both fluorescent genes are suitable for setting up a transformation system. The antibiotics hygromycin and kanamycin successfully prevented the growth of untransformed tissues, but the antibiotic timentin successfully prevented the growth of bacteria A. t. after the transformation.